Propuestas curriculares para responder a la diversidad del alumnado de primaria desde contextos inclusivos - Asunción Jiménez Trens (Universidad de La Rioja, 2013)
This study set off a serial of arguments that show the necessity of a model of educative inclusion as a doubtless quality factor in the system education. A model that finds its sense just in achieve an educative answer fitted with the diversity of the heterogeneous students who integrate the schools and the classrooms. This model tries, therefore, to provoke a reflection and to debate about how inside common curricular environment different opportunities can be offered to all the students, allowing an individual and personalized education. Taking these considerations into account and with no intention of being exhaustive, some proposals are presented as guidelines for both the design and development of the school curriculum: Educative Project, Curricular Project and Classroom Planning.